Allogeneic hematopoietic cell transplantation in older myelofibrosis patients: A study of the chronic malignancies working party of EBMT and the Spanish Myelofibrosis Registry. Issue 10 (8th July 2021) - Hernández‐Boluda, Juan‐Carlos; Pereira, Arturo; Kröger, Nicolaus; Cornelissen, Jan J.; Finke, Jürgen; Beelen, Dietrich; de Witte, Moniek; Wilson, Keith; Platzbecker, Uwe; Sengeloev, Henrik; Blaise, Didier; Einsele, Hermann; et al.
Abstract: Allogeneic hematopoietic cell transplantation (allo‐HCT) is increasingly used in older myelofibrosis (MF) patients, but its risk/benefit ratio compared to non‐transplant approaches has not been evaluated in this population. We analyzed the outcomes of allo‐HCT in 556 MF patients aged ≥65 years from the EBMT registry, and determined the excess mortality over the matched general population of MF patients ≥65 years managed with allo‐HCT (n = 556) or conventional drug treatment (n = 176). The non‐transplant cohort included patients with intermediate‐2 or high risk DIPSS from the Spanish Myelofibrosis Registry. After a median follow‐up of 3.4 years, the estimated 5‐year survival rate, non‐relapse mortality (NRM), and relapse incidence after transplantation was 40%, 37%, and 25%, respectively. Busulfan‐based conditioning was associated with decreased mortality (HR: 0.7, 95% CI: 0.5–0.9) whereas the recipient CMV+/donor CMV‐ combination (HR: 1.7, 95% CI: 1.2–2.4) and the JAK2 mutated genotype (HR: 1.9, 95% CI: 1.1–3.5) predicted higher mortality. Busulfan‐based conditioning correlated with improved survival due to less NRM, despite its higher relapse rate when compared with melphalan‐based regimens. Excess mortality was higher in transplanted patients than in the non‐HCT cohort in the first year of follow‐up (ratio: 1.93, 95% CI: 1.13–2.80), whereas the opposite occurred between the fourth and eighth follow‐up years (ratio: 0.31, 95% CI: 0.18–0.53). Comparing the excess mortality of the two treatments, male patients seemed to benefit more than females from allo‐HCT, mainly due to their worse prognosis with non‐transplant approaches. These findings could potentially enhance counseling and treatment decision‐making in elderly transplant‐eligible MF patients.